2007
DOI: 10.1529/biophysj.106.102780
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Firefly Luciferase Inhibition by General Anesthetics: Gaussian and Anisotropic Network Analyses

Abstract: The new crystal structures of the product-bound firefly luciferase combined with the previously determined substrate-free structures allow for a detailed analysis of the dynamics basis for the luciferase enzymatic activities. Using the Gaussian network model and the anisotropic network model, we show here that the superposition of the three slowest anisotropic network model modes, consisting of the bending, rotating, and rocking motions of the C-domain, accounts for large rearrangement of domains from the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 47 publications
4
47
0
Order By: Relevance
“…The high-resolution structure 1BA3 was chosen to be applied with MD simulation for two reasons. Firstly, the root mean-square deviation (RMSD) between 1LCI and 1BA3 is very small (b1 Å), consistent with the fact that 1BA3 was obtained by simply soaking the apoluciferase crystal transiently in a saturated bromoform solution [25]. Secondly, there are only two residues unresolved in 1BA3 while there are more than twenty residues missed in 1LCI.…”
Section: Analysis Of Flexibilitysupporting
confidence: 61%
“…The high-resolution structure 1BA3 was chosen to be applied with MD simulation for two reasons. Firstly, the root mean-square deviation (RMSD) between 1LCI and 1BA3 is very small (b1 Å), consistent with the fact that 1BA3 was obtained by simply soaking the apoluciferase crystal transiently in a saturated bromoform solution [25]. Secondly, there are only two residues unresolved in 1BA3 while there are more than twenty residues missed in 1LCI.…”
Section: Analysis Of Flexibilitysupporting
confidence: 61%
“…First, because of its hydrophobic nature, site 4 closed had a negligible number of water molecules within a 7-A radius of the binding site before and after halothane binding. It is not surprising to see a relatively low probability (1/12, 8%) for this scenario, considering that anesthetics prefer an amphiphilic environment 20, 3739. Second, the number of water molecules within 7 A from the center of site 6 closed and site 2 open (2/12, 17%) increased slightly.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent MD simulations demonstrated that halothane altered the global motion of the α4β2 nAChR more in the open channel conformation than in the closed channel conformation,12, 13 suggesting that anesthetic inhibition to the α4β2 nAChR function might result from the anesthetic perturbation to the motion of the open channel. It is possible that water facilitates the anesthetic disturbance to the protein global motions that are essential for protein function 12, 18–20…”
Section: Introductionmentioning
confidence: 99%
“…[34] Another type of inhibition was discovered unexpectedly some 40 years ago: general anesthetics, for example, N-decanol, are strong inhibitors of firefly luciferase. [35] Structurally related aliphatic compounds (dodecanol, dodecanoic acid, dodecylamine) are also able to completely quench the luminescence reaction. [36] We suggest that SDSF acts as a substrate analogue and inhibits the luciferase reaction.…”
Section: Discussionmentioning
confidence: 99%